A Treatise on Efficacy: Between Western and Chinese Thinking - and Jullien, Francois (University of Hawaii Press, 2004)
In this highly insightful analysis of Western and Chinese concepts of efficacy, Francois Jullien subtly delves into the metaphysical preconceptions of the two civilizations to account for diverging patterns of action in warfare, politics, and diplomacy. He shows how Western and Chinese stategies work in several domains (the battle-field, for example) and analyzes two resulting acts of war. The Chinese strategist manipulates his own troops and the enemy to win a battle without waging war and to bring about victory effortlessly. Efficacity in China is thus conceived of in terms of transformation (as opposed to action) and manipulation, making it closer to what is understood as efficacy in the West. Jullien's brilliant interpretations of an array of recondite texts are key to understanding our own conceptions of action, time, and reality in this foray into the world of Chinese thought. In its clear and penetrating characterization of two contrasting views of reality from a heretofore unexplored perspective, Treatise on Efficacy will be of central importance in the intellectual debate between East and West.